THE INFLUENCE OF E-PORTFOLIO TOWARD THE PROCESS AND THE QUALITY OF STUDENTSâ TRANSLATION - Rahmawati, Maya; Hakim, Putri Kamalia (ELTICS : Journal of English Language Teaching and English Linguistics, 2017)
Abstract Translation in its nature is a complex act of communication. Therefore, in translation course for undergraduate students conventional assessment should not be the only way to assess their learning. This is due to the fact that such kind of assessment mainly focus on the product rather than the process, while 90% of learning activitiy in translation course involves practice. One of the assessment technique which is higly potential to thoroughly assess both the process and quality of studentsâÂ  translation is alternative assessment using e-portfolio.This paper investigates the use of e-portfolio in translation course for undergraduate students. It aims to find out the extent to which e-portfolio as an alternative assessment influences the process and quality of studentâs translation. It was found that e-portfolio influenced the studentsâ translation ability wherethe value is Sig. = 0,001 < Î± = 0,05. The studentsâ translation test were also analyzed using comparative method to describe which aspect of the three criteria has the e-portfolio influenced studentsâ test score. It was discovered that 82 % students achieved higher score inacceptability. While 62% students achieved higher score in accuracy, and only 56% of students achieved higher score in readability. In terms of translation process, e-portfolio helps students track their progress, give and receive feedback from various participants, as well as have virtual room to sort their works which are easily accessible. Keyword: e-portfolio, translation, assessment, alternative assessment